Lemma (Impl). (P ==> Q) <==> (P \/ Q) <==> Q. Proof. We parse the formula to be proved as ((P ==> Q) <==> (P \/ Q)) <==> Q, and start from the left hand side, since it is more complex. P ==> Q <==> P \/ Q <==> {by def. of implication} (!P \/ Q) <==> P \/ Q <==> {by disjunction distributes over the equivalence, to pull Q out of both sides} !P \/P <==> Q <==> {by law of the excluded middle} true <==> Q <==> {by predicate calculus} Q Lemma (weakening) X ==> X \/ Y. Proof: We tried this in different ways, but what worked was the suggestion to reduce the entire formula to true. X ==> X \/ Y = {by def. of implication} !X \/ X \/ Y = {by !A \/ A = true} true \/ Y = {by true is the zero of disjunction} true